2021
DOI: 10.1186/s12913-021-06807-4
|View full text |Cite
|
Sign up to set email alerts
|

From centralized DRG costing to decentralized TDABC-assessing the feasibility of hospital cost accounting for decision-making in Denmark

Abstract: Background The objective is to examine hospital cost accounts to understand the foundation upon which healthcare decisions are based. More specifically, the aim is to add insights to accounting practices and their applicability towards a newly establish value-based agenda with a focus on patient-level cost data. Methods We apply a cost accounting framework developed to position and understand hospital cost practices in relation to government requir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Cost control, on the other hand, has a broader scope. The existing study discusses a number of cost-control specifics such as staff motivation and goal alignment and approach evaluation ( Malmmose and Lydersen, 2021 ). Kaplan claims that “money invested inside the environment and in communities does not have to be for selfless reasons alone.” The truthfulness of this claim may be true in the short-term.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Cost control, on the other hand, has a broader scope. The existing study discusses a number of cost-control specifics such as staff motivation and goal alignment and approach evaluation ( Malmmose and Lydersen, 2021 ). Kaplan claims that “money invested inside the environment and in communities does not have to be for selfless reasons alone.” The truthfulness of this claim may be true in the short-term.…”
Section: Review Of Literaturementioning
confidence: 99%
“…TDABC has been applied to several care and services pathways in various areas of healthcare. For example, it has been used in studies on care pathways in surgery, oncology, cardiology, mental health, rehabilitation, and teleconsultation [9][10][11][12][13] . These studies have shown that TDABC can be an effective activity-costing method throughout the care pathway, providing valuable information to manage costs and improve departmental e ciency [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the TDABC model facilitates the costing of different care pathways or healthcare departments 8,10,11,14 . Some studies have also compared care pathways by analysing costs according to different models.…”
Section: Introductionmentioning
confidence: 99%
“…As clinicians have a direct impact on 35%-60% of a hospital's total expenses [1], medical personnel in (German) hospitals are suspected of making decisions for the sake of maximizing pro ts [2]. Previous studies in European countries have already addressed this issue and found that apparent cost-driven decisions by medical personnel are countered by the lack of knowledge for economic decision making as they do not know the costs of medical supplies or interventions [3][4][5][6]. Therefore, cost-driven decisions might be based on a hunch at best [7][8][9].…”
Section: Introductionmentioning
confidence: 99%